The Influence of Work Motivation on the Work Productivity of PT Employees. GS Battery Karawang - Sari, Euis Widia; Kristanto, Yudi; Army, Widya Lelisa (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is motivated by the problem of lack of work motivation resulting in a problem phenomenon regarding a decrease in employee work productivity, where employees seem to get bored easily with the routine work they do and the work environment is less supportive, resulting in employees being less comfortable doing their work. The aim of this research is to determine the influence of work motivation on employee work productivity. This research using quantitative methods with associative techniques was carried out at PT. GS Battery Karawang with a population of 35 employees with data collection techniques using questionnaires. Based on the calculation results, the correlation coefficient is r = 0.897 and the determination coefficient is R = r2 = 0.486. Testing the significance of the correlation obtained tcount (5.582) > t table (2.021) at  = 0.05, indicating that the correlation coefficient is significant. Thus, the research hypothesis which states that there is a relationship between work motivation and work productivity can be accepted. This means that the better a person's work motivation will be followed by higher work productivity. Meanwhile, the coefficient of determination of 0.486 shows that 48.6% of the variation in Work Productivity can be explained by variations in Work Motivation, the remaining 51.4% is determined by other factors outside Work Motivation.